Banach algebra generated by a finite number of bergman polykernel operators, continuous coefficients, and a finite group of shifts - Mozel’, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study the Banach algebra generated by a finite number of Bergman polykernel operators with continuous coefficients that is extended by operators of weighted shift that form a finite group. By using an isometric transformation, we represent the operators of the algebra in the form of a matrix operator formed by a finite number of mutually complementary projectors whose coefficients are Toeplitz matrix functions of finite order. Using properties of Bergman polykernel operators, we obtain an efficient criterion for the operators of the algebra considered to be Fredholm operators.